Surface Electromyographic Activity of the Hamstring Muscles During Isometric Prone Leg Curls: A Pilot Study - Toshiaki Soga; Taspol Keerasomboon; Rami Mizuta; Norikazu Hirose (International Journal of Athletic Therapy and Training, 2026)
This study aimed to investigate the surface electromyography (sEMG) activity of hamstring muscles—biceps femoris long head, semitendinosus, semimembranosus, and biceps femoris short head—during isometric prone leg curls at 15°, 45°, 75°, and 105° of knee flexion (0° was considered full extension). Thirteen recreationally active men participated in this study. Results revealed that the biceps femoris short head sEMG activity increased with deeper knee flexion angles. However, the biceps femoris long head and semimembranosus sEMG activities increased with shallower flexion angles, and semitendinosus’s sEMG activity was unaffected. Therefore, to maximize biceps femoris short head activation, deep knee flexion angles might be more advantageous.